The efficacy of radical antegrade modular pancreatosplenectomy: A systematic review and meta‐analysis - Watanabe, Jun; Rifu, Kazuma; Sasanuma, Hideki; Kotani, Kazuhiko; Sata, Naohiro (Journal of hepato-biliary-pancreatic sciences, 2022)
Background/Purpose Previous systematic reviews have shown that radical antegrade modular pancreatosplenectomy (RAMPS) had favorable outcomes including prognosis. However, recent large studies have shown opposite results, thus necessitating clarification of RAMPS efficacy. We aimed to update existing evidence on the clinical outcomes of RAMPS for left‐sided pancreatic cancer by comparing them to those of the conventional approach. Methods Electronic databases and registries were searched until August 2021 to perform random‐effect meta‐analysis. Methodological quality was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation approach. The protocol was registered at protocols.io (https://doi.org/10.17504/protocols.io.bxhfpj3n). Results Thirteen cohort studies (1641 patients) and four ongoing randomized controlled trials (RCTs) were identified. RAMPS increased disease‐free survival (hazard ratio [HR] 0.62, 95% confidence interval [CI] = 0.42‐0.91), but it had little effect on overall survival (HR 0.92, 95% CI = 0.79‐1.09) and recurrence‐free survival (HR 0.72, 95% CI = 0.37‐1.38) with low certainty of evidence. Conclusion The meta‐analysis of recent studies suggests that RAMPS may have little effect on clinical outcomes. These findings highlight the necessity of further studies, including RCTs to determine the efficacy and subsequent indication of RAMPS in clinical cases.